Economia ambiental, economia ecológica e consumo sustentável: uma análise de convergências teóricas - (:unkn) unknown (Universidade Federal do Pampa, 2023)
When looking at the evolution and consumption practices of a society, it can be said that they are a reflection of the cultural landscape in which they are immersed. The act of consuming is a manifestation of individual behaviors but also reflects history, culture, and socially constructed conventions. Contemporary accumulative and unrestricted consumption has been questioned, and there is a proposal for its replacement with another type of consumption known as conscious or sustainable consumption. Studies on this topic are still recent and limited, making it difficult to classify this discussion as typical of a specific field within economics. In this context, the aim is to analyze, through a systematic literature review, and theoretical essay the characteristics that are developing in studies on sustainable consumption, seeking convergences between them and the characteristics of the main fields of environmental discussion in economics. The research is proposed as exploratory and comparative, with qualitative characteristics. Bibliographic research will be used as a technique to deepen the knowledge of Ecological Economics and Environmental Economics, and a literature systematic review will be used for the topic of sustainable consumption. In addition to publications in books, dissertations, and theses, the following sources of information will be used: Scientific Electronic Library Online; Educational Resources Information Center - ERIC; Web of Science; Brazilian Digital Library of Theses and Dissertations, Considering that the achieved result indicates that Sustainable Consumption exhibits convergences with both Ecological Economics and Environmental Economics, and taking into account that the subject is considered relatively new within the academic landscape, this limits the scope of the searches.
Keywords: Economia ambiental; Economia ecológica; Consumo sustentável; Consumo consciente; Environmental economics; Ecological economics; Sustainable consumption; Conscious consumption; CNPQ::CIENCIAS SOCIAIS APLICADAS